Nitrous oxide (N2O) measurements in managed soil under grazing with dairy cattle - Núñez-Ramos, Pedro Antonio; García-Lagombra, Gregorio; Caridad del Rosario, Joaquín; Asencio-Cuello, Víctor José (REVISTA TERRA LATINOAMERICANA, 2021)
Nitrous oxide (N2O) emissions measurements in livestock systems in the Dominican Republic are a priority for its government. The N2O has been responsible for 5% of total GHG (greenhouse gas) in the last 100 years. In Dominican livestock, various nitrogen fertilizers and amendments are used to increase the productivity these systems. However, if these fertilizers are not properly managed, these could generate N2O emissions. Therefore, our research was carried out with the aim of quantifying N2O emissions from grazing forage with dairy cattle. A Bermuda grass pasture (Cynodon dactylon) from Casa de Alto, Dominican Republic was used. The study was conducted during the period of June – August, 2018. A completely randomized sub-divided plot design was used with three factors, four repetitions and three treatments (urine, urea, and control). Closed-flow PVC chambers were used to obtain gas samples and determine N2O emissions. In addition, climatic factors, nitrogen (N) in urine, soil and grass were recorded. Data were analyzed with the InfoStat statistical software. The N2O emissions averaged the following values: 0.56 mg L-1 for control, 1.02 mg L-1 for urine and 1.18 mg L-1 for urea. The only treatment that showed statistical differences with the control (P < 0.05) was urea. Emissions were 5.6, 10.2 and 11.8 kg ha-1 for the control, urine and urea, respectively, with high emissions compared to results obtained in other research in the country.